2018
DOI: 10.14214/sf.9980
|View full text |Cite
|
Sign up to set email alerts
|

Development of height growth and frost hardiness for one-year-old Norway spruce seedlings in greenhouse conditions in response to elevated temperature and atmospheric CO<sub>2</sub> concentration

Abstract: Development of height growth and frost hardiness for one-year-old Norway spruce seedlings in greenhouse conditions in response to elevated temperature and atmospheric CO 2 concentrationLevkoev E., Mehtätalo L., Luostarinen K., Pulkkinen P., Zhigunov A., Peltola H. (2018). Development of height growth and frost hardiness for one-year-old Norway spruce seedlings in greenhouse conditions in response to elevated temperature and atmospheric CO 2 concentration. Silva Fennica vol. 52 no. 3 article id 9980. 15 p. http… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In September, the seedlings with healthy needles were capable of hardening with decreasing air temperatures between the box opening and the freezing tests. The increased temperatures inside the boxes may also have delayed FH development, because elevated temperatures can delay the onset of FH in Norway spruce seedlings [45].…”
Section: Autumn Frost Hardiness Of Norway Spruce Seedlingsmentioning
confidence: 99%
“…In September, the seedlings with healthy needles were capable of hardening with decreasing air temperatures between the box opening and the freezing tests. The increased temperatures inside the boxes may also have delayed FH development, because elevated temperatures can delay the onset of FH in Norway spruce seedlings [45].…”
Section: Autumn Frost Hardiness Of Norway Spruce Seedlingsmentioning
confidence: 99%
“…To our knowledge, there have been no studies of the responses of different genotypes of either Scots pine or Norway spruce to fluctuating winter temperatures. However, it has been observed that autumn frost hardening of one-year-old Norway spruce seedlings varies between genotypes when growing season temperatures increase (Levkoev et al 2018). In addition, the two-year-old seedlings received a short day treatment in July, but the one-year-old seedlings did not, which may have led to differences in responses to acclimation treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This may be one reason for the reduced FH in the box-stored seedlings in early August. In addition, temperatures were higher inside the boxes (Study I: Figure 2), which may have delayed the development of FH in Norway spruce seedlings (Levkoev et al 2018). Also, the lowered photosynthetic capacity of the seedlings stored in boxes over a week indicates a reduction in FH since it is dependent on the current photosynthates available (van den Driessche 1970).…”
Section: Duration Limits Of Different Field Storage Methodsmentioning
confidence: 99%